Detection and Quantification of Class I Caries with Laser Fluorescence Technique - Jameel, Rana T.; Jawad, Hussein A. (Iraqi Journal of Laser, 2010)
The objective of the present study is to verify the actual carious lesion depth by laserfluorescence technique using 650 nm CW diode laser in comparison with the histopathologicalinvestigation. Five permanent molar teeth were extracted from adult individuals for different reasons(tooth impaction, periodontal diseases, and pulp infections); their ages were ranging from 20-25 yearsold. Different carious teeth with varying clinical stages of caries progression were examined. Anexperimental laser fluorescence set-up was built to perform the work regarding in vitro detection andquantification of occlusal dental caries and the determination of its actual clinical carious lesion depth by650 nm CW diode laser (excitation wavelength (λexcit.) = 669 nm). Five teeth were sent tohistopathological examination to confirm the efficacy of laser fluorescence technique for thedetermination of actual carious lesion depth. The results are leading to the detection of carious lesions fordifferent depths. The deepest carious lesions revealed high fluorescence intensity. Based on thesefindings; it was concluded that 650 nm CW diode laser (λexcit. = 669 nm 40 mW) is a suitable and areliable tool for caries diagnosis and depth assessment. Histopathological findings for the estimation ofactual carious lesion depth revealed a good correlation with that of laser fluorescence technique.